Association between PM2.5 and PM2.5 Constituents and Preterm Delivery in California, 2000–2006. Issue 5 (21st July 2017) - Basu, Rupa; Pearson, Dharshani; Ebisu, Keita; Malig, Brian
Abstract: Background: Particulate matter (PM) has been documented to contribute to preterm delivery. However, few studies have investigated the relationships between individual constituents of fine PM (PM2.5 ) and preterm delivery, and factors that may modify their associations. Methods: In this study, we examined the associations between several prenatal exposure metrics to PM2.5 and 23 constituents of PM2.5 and preterm delivery in California from 2000 to 2006. In a retrospective cohort study including 231 637 births, we conducted logistic regression analyses adjusting for maternal, infant, temporal, geographic, and neighbourhood characteristics. Results: We observed increased risk for preterm delivery with full‐gestational exposure for several PM2.5 constituents. Per interquartile range increase, ammonium (21.2%, 95% confidence interval (CI) 17.1, 25.4), nitrate (18.1%, 95% CI 14.9, 21.4) and bromine (16.7%, 95% CI 13.2, 20.3) had some of the largest increased risks. Alternatively, some PM2.5 constituents were inversely associated with preterm delivery, including chlorine (−8.2%, 95% CI −10.3, −6.0), sodium (−13.2%, 95% CI −15.2, −11.3), sodium ion (−11.9%, 95% CI −14.1, −9.6) and vanadium (−19.2%, 95% CI −25.3, −12.6). Greater associations between PM2.5 constituents and preterm delivery were observed for Blacks and Asians, older mothers, and those with some college education compared to their reference groups, as well as for births with gestational ages from 32 to 34 weeks. Conclusions: PM2.5 constituents ammonium, nitrate and bromine, often linked to traffic and biomass combustion, were most associated with increased risk of preterm delivery in California. Certain demographic subgroups may be particularly impacted.